Comparison of CHROMagar Orientation versus CLED (cystine-lactose-electrolyte-deficient) Agar, VITEK-XL and MALDI-TOF in a Tertiary Laboratory Setting Processing Urine Culture Samples at Dr Lal Path Labs, Delhi (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: urine culture; CHROMagar orientation; CLED agar; presumptive identification.